Characteristics of sports activities in the training of young volleyball players in children and teenagers sports schools - Turapova Shoxsanam Kholmurod qizi (International Journal on Orange Technologies, 2021)
This article discusses the specifics of sports training and its content in the training of young volleyball players in children and youth sports schools.